Effect of ZrO2 whiskers on the microstructure and mechanical properties of a Ti(C, N)‐based cermet cutting tool material. Issue 4 (25th March 2019) - Fang, Yihang; Zhao, Xianrui; Zhang, Mengxian; Zhang, Ping; Cheng, Hu; Xue, Shuangxi; Zhang, Li; Wu, Jianbo; Feng, Shangshen
Abstract: ZrO2 ‐whisker‐reinforced Ti(C, N)‐based cermets were designed and prepared via a vacuum hot‐pressing process. The ZrO2 whisker characteristics and the phase, microstructure and mechanical properties of the cermets were investigated, and the relevant toughening mechanisms were examined. The results indicate that the ZrO2 whiskers retain their morphology and significantly improve the mechanical properties of the cermets. The relative density and hardness decreased slightly with increasing ZrO2 whisker content. At a whisker content of 7.5 wt.%, the fracture toughness and flexural strength reached their maximum values of 7.825 MPa·m 1/2 and 1094 MPa, respectively. This enhancement in the mechanical properties is due to stronger bonding between the interfaces through dimples, tearing ridges and whisker pull‐out, in addition to the inhibition of crack propagation via crack deflection, crack branching and crack bridging.